Biomarkers of renal transplant fibrosis - O. R. Bystrova; E. A. Stakhanova; M. I. Ilchuk; A. A. Ulybysheva; O. E. Gichkun; D. A. Saydulaev; O. P. Shevchenko (Вестник трансплантологии и искусственных органов)
Fibrosis is one of the causes of kidney allograft loss, especially late after transplantation (up to 65% incidence after 2 years). The purpose of this literature review is to analyze studies examining noninvasive monitoring techniques for renal graft fibrosis.